Comparative proteomics analysis of human stem cells from dental gingival and periodontal ligament. Issue 11 (30th March 2022) - Lei, Tong; Wang, Jian; Liu, Yanyan; Zhang, Xiaoshuang; Du, Hongwu
Abstract: Dental stem cells isolated from oral tissues have been shown to provide with high proliferation ability and multilineage differentiation potential. Gingival mesenchymal stem cells (GMSCs) and periodontal ligament stem cells (PDLSCs), kinds of dental stem cells, can be used as substitutes for tissue repair materials because of their similar regenerative functions. In this study, we aim to explore the similarities and differences between the protein profiles of GMSCs and PDLSCs through quantitative proteomics. A total of 2821 proteins were identified and retrieved, of which 271 were upregulated and 57 were downregulated in GMSCs compared to PDLSCs. Gene Ontology (GO) analysis demonstrated that the 328 differentially abundant proteins (DAPs) were involved in the regulation of gene expression, metabolism, and signal transduction in biological process, mainly distributed in organelles related to vesicle transport, and involved in the molecular function of binding protein. And Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis showed that the DAPs were committed to regulating the synthesis of proteasome and spliceosome. Real‐time quantitative polymerase chain reaction (RT‐qPCR) results showed that ARPC1B, PDAP1, and SEC61B can be used as special markers to distinguish GMSCs from PDLSCs. This research contributes to explaining the molecular mechanism and promoting the clinical application of tissue regeneration of GMSCs and PDLSCs.